2016
DOI: 10.1080/17501229.2016.1134859
|View full text |Cite
|
Sign up to set email alerts
|

Roles and scaffolding in teletandem interactions: a study of the relations between the sociocultural and the language learning dimensions in a French–Chinese teletandem

Abstract: International audienceOur paper aims to present students’ interactions in a teletandem – that is, tandem through desktop videoconference [Telles, J., ed. 2009. Teletandem. Um contexto virtual, autônomo, colaborativo para aprendizagem das linguas estrangeiras no século XXI. Campinas, SP: Pontes Editores] – telecollaborative project between third-year undergraduate students in a Chinese university and first-year graduate students in a French university. More precisely, we aim to find possible relations between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Data Sets and Participants Our data consist of 10 hours of online interactions of university students that are L2 users of a foreign language. The video-based data stem from the Teletandem Dalian-Lille project (Cappellini, 2016), where four French-Chinese pairs were engaged in free teletandem conversations. Two students from partner universities in France and China interacted through video chat to help each other learn their respective L1s.…”
Section: Methods and Designmentioning
confidence: 99%
“…Data Sets and Participants Our data consist of 10 hours of online interactions of university students that are L2 users of a foreign language. The video-based data stem from the Teletandem Dalian-Lille project (Cappellini, 2016), where four French-Chinese pairs were engaged in free teletandem conversations. Two students from partner universities in France and China interacted through video chat to help each other learn their respective L1s.…”
Section: Methods and Designmentioning
confidence: 99%
“…Some studies emphasize that direct contact with native speakers improves language competences in all areas, especially in communicative uses (Belz & Thorne, 2006;Chun, 2008). Cappellini (2016) has observed that some conversational actions occur online more often than offline, thus supporting the idea that this new format might offer new affordances for language learning (cf. Jianqi & Yuping, 2010).…”
Section: Impact Of Online Lementioning
confidence: 99%
“…In our study we analyse data from two pedagogical settings. The first one is the Teletandem Dalian-Lille project (Cappellini 2014a(Cappellini , 2016, a teletandem between third year undergraduate students learning French at the Dalian University of Foreign Languages in China and first year graduate students learning Chinese at the Lille3 University in France. Students had an intermediate proficiency level in their target language.…”
Section: Contextsmentioning
confidence: 99%
“…Within the socio-interactionist approach, many authors have identified different types of conversational side sequence (Jefferson 1972) in which the mediational work of joint attention driving the internalization of symbolic instruments at the microgenetic level (Wertsch 1985) can be observed. From among these types of side sequence (see Cappellini 2016), in this study we selected "sequences of normative evaluation" (séquences d'évaluation normative, hereafter SEN) identified and described by Py (2000). Py defines SENs as side sequences starting when a native speaker/expert interlocutor takes the unsolicited initiative to repair the utterance of a non-native speaker/learner.…”
Section: Sequences Of Normative Evaluationmentioning
confidence: 99%
See 1 more Smart Citation